A Analysis of Climber Students' Mathematics Communication Skills in Solving Algebraic Problems - Prayogo; Hanim Faizah; Susilo Hadi (Buana Pendidikan, 2023)
This study aims to describe students' mathematical communication skills in the climber category. Subjects in this study were selected based on the results of the ARP test. The techniques used in this study were tests and interviews with climber students who were selected from class VII junior high school students. For data analysis, the Miles and Huberman method was used. The results of this study are climber students are able to fulfill all the established mathematical communication indicators. Climber students are able to express real objects, situations and everyday events in the form of mathematical models (in the form of pictures, tables, diagrams, graphs, algebraic expressions), explain ideas and mathematical models (in the form of pictures, tables, diagrams, graphs, expressions algebra) into spoken or written language, Explain and create mathematical questions being studied, Listen, discuss, and write about mathematics, and Make conjectures, construct arguments, formulate definitions and generalizations.